Cloud dynamics over the geologically active zones of Ukraine: diagnostic and predictive numerical modeling, surface and satellite observations - T. A. Beliy; A. M. Pirnach (Геофизический журнал, 2012)
Dynamics of cloudiness above geologically active regions of Ukraine is studied on an example of the Crimean peninsula based on satellite pictures, data of surface meteorological observation stations and diagnostic and prognostic numerical simulation. The event on September 20, 2002 has been chosen as an example. An earthquake of class K = 8,8 with epicenter coordinates 44,77° n. l., 37,12 ° e. l., which happened during that period at 20 h 42 in the Crimea. Morphological changes were registered on the satellite pictures of cloudiness as linear cloudy anomalies (LCA) eight hours before the earthquake. LCA was located above geological fault, which separated the Scythian plate and the Crimean meganticlinorium. Numerical analysis of cloudiness evolution demonstrated that one of the possible factors of LCA appearance above geological faults of the Earth is inhomogeneous distribution of positive and negative anomalies of gravity force.